Controlled Random Search Optimization for Linear Antenna Arrays - S. M. Meriah; F. T. Bendimerad; L. Merad (Radioengineering, 2006)
An optimization problem for designing nonuniformly spaced, linear antenna's arrays is formulated and solved by means of a controlled random search algorithm. The proposed iterative method aims at a linear array and the optimization of element positions and excitations coefficients by minimizing the side-lobes level and respecting a beam pattern shape. Selected examples are included, which demonstrate the effectiveness and the design flexibility of the proposed method in the framework of the electromagnetic synthesis of linear antenna arrays.